Daya Anti Bakteri Kombinasi Fosfomisin dan Sulbaktam-sefoperazon terhadap Bakteri Pseudomonas aeruginosa - Agus Syahrurachman; Fera Ibrahim; Atna Permana (Majalah Kedokteran Indonesia, 2019)
Introduction: Pseudomonas aeruginosa may cause infections in various organs. Due to increase resistance, single antibiotic option for treatment of those infections is more limited.Objective: to elcucidate in vitro antibacterial effect of fosfomycin and sulbactam-cefoperazone alone and its combination against clinical isolates of Pseudomonas aeruginosa.Methods: Minimal Inhibitory concentration of fosfomycin and cefoperazone-sulbactam as a single drug and their combination was determined in liquid media against 30 clinical isolates of the Pseudomonas aeruginosa. Effect of antibiotic combination was calculated by Fraction Inhibitory Index. Time-kill curve was plotted according to the number of viable bacteria after antibiotic exposure.Results: The proportion of susceptible isolate to sulbactam-cefoperazon alone was 66.7% and increased to 90 % to combined antibiotics. Proportion of susceptible bacteria to fosfomycin alone was 10 % and increase to 20 % to combined antibiotics. Synergistic, indifferent and antagonistic effects were found in 60%,36.7% and 3.3% strains respectively. Rapid bacterial death occurred within the first 4 hours of exposure.Conclusion : Combination of sulbactam-cepoferazone and fosfomycin have sinergism in majority of tested strain of Ps aeruginosa and only one strain show antagonistic effect.